Deterministic modesl for growth analysis and forecasting fo rice production in Bangladesh - Awal, MA; Haque, ME; Imam, MF (Bangladesh Journal of Agricultural Research, 2008)
The present study was undertaken to find out appropriate model using seven contemporary model selection criteria that could best describe the growth pattern of rice production in Bangladesh and its three type seasons (aus, aman and boro during the time period 1969-70 to 2005-2006). It appeared from the study that the best fitting model for aus and boro rice production was cubic model and quadratic model. It means that the assumption of constant annual rate of growth in percent that lies behind the use of exponential/compound model, which was very common to use in describing growth pattern, was not true for the growth pattern of rice production in aus and boro. In aman rice production, exponential/compound model seemed to be appropriate. Five years forecasting results showed that the aus, aman, and boro rice production in the year of 2005/06 were 1.83, 11.30, and 14.23 million metric tons with a 95 percent confidence interval, respectively. If the present growth rates continue then the total aus, aman, and boro rice production in Bangladesh will be 2.28, 12.13, and 17.29 million metric tons in the year of 2009/10, respectively. Bangladesh J. Agril. Res. 32(4) : 603-620